Plant Parasitic Nematodes in Sustainable Agriculture of North America Vol.2 - Northeastern, Midwestern and Southern USA (Sustainability in Plant and Crop Protection, 2018)
Plant-parasitic nematodes are recognized as one of the greatest threats to crop production throughout the world. Estimated annual crop losses of $8 billion in the United States and $78 billion worldwide are attributed to plant parasitic nematodes. Plant parasitic nematodes not only cause damage individually but form disease-complexes with other microorganisms thereby increasing crop loss. Nematode diseases of crops are difficult to control because of their insidious nature and lack of specific diagnostic symptoms which closely resemble those caused by other plant pathogens and abiotic diseases. Future developments of sustainable management systems for preventing major economical agricultural losses due to nematodes is focused on strategies that limit production costs, enhance crop yields, and protect the environment. This book presents a first compendium and overview for nematode problems and their management across North America. Each chapter provides essential information on the occurrence and distribution of plant parasitic nematodes, their major crop hosts, impact on crop production and sustainable management strategies for each region of the continent including, Canada, Mexico and all states of the USA. For each region, a thematic overview of changes in crop production affected by plant parasitic nematodes and their management strategies over time will provide invaluable information on the important role of plant parasitic nematodes in sustainable agriculture.